Influence of Stress and Antibiotic Resistance on Cell-Length Distribution in Mycobacterium tuberculosis Clinical Isolates - Vijay, Srinivasan; Vinh, Dao N.; Hai, Hoang T.; Ha, Vu T. N.; Dung, Vu T. M.; Dinh, Tran D.; Nhung, Hoang N.; Tram, Trinh T. B.; Aldridge, Bree B.; Hanh, Nguyen T.; Thu, Do D. A.; Phu, Nguyen H.; et al. (Frontiers in Microbiology, 2017)
Mycobacterial cellular variations in growth and division increase heterogeneity in cell length, possibly contributing to cell-to-cell variation in host and antibiotic stress tolerance. This may be one of the factors influencing Mycobacterium tuberculosis persistence to antibiotics. Tuberculosis (TB) is a major public health problem in developing countries, antibiotic persistence, and emergence of antibiotic resistance further complicates this problem. We wanted to investigate the factors influencing cell-length distribution in clinical M. tuberculosis strains. In parallel we examined M. tuberculosis cell-length distribution in a large set of clinical strains (n = 158) from ex vivo sputum samples, in vitro macrophage models, and in vitro cultures. Our aim was to understand the influence of clinically relevant factors such as host stresses, M. tuberculosis lineages, antibiotic resistance, antibiotic concentrations, and disease severity on the cell size distribution in clinical M. tuberculosis strains. Increased cell size and cell-to-cell variation in cell length were associated with bacteria in sputum and infected macrophages rather than liquid culture. Multidrug-resistant (MDR) strains displayed increased cell length heterogeneity compared to sensitive strains in infected macrophages and also during growth under rifampicin (RIF) treatment. Importantly, increased cell length was also associated with pulmonary TB disease severity. Supporting these findings, individual host stresses, such as oxidative stress and iron deficiency, increased cell-length heterogeneity of M. tuberculosis strains. In addition we also observed synergism between host stress and RIF treatment in increasing cell length in MDR-TB strains. This study has identified some clinical factors contributing to cell-length heterogeneity in clinical M. tuberculosis strains. The role of these cellular adaptations to host and antibiotic tolerance needs further investigation.